2012
DOI: 10.1002/bdd.1774
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on altered hepatic metabolism of CYP3A substrates in rats with glycerol‐induced acute renal failure

Abstract: To examine the mechanism accounting for the diverse alteration of hepatic metabolism of CYP3A substrates observed with renal function being severely impaired, the hepatic drug metabolizing activity was evaluated using liver microsomes prepared from rats with glycerol-induced acute renal failure (ARF). Midazolam, nifedipine and rifabutin were employed as representative CYP3A substrates. When the Michaelis-Menten parameters, K(m) and V(max) , were examined in the incubation study, the K(m) values of midazolam an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 37 publications
(53 reference statements)
0
28
0
Order By: Relevance
“…However, several studies in rats (1)(2)(3)(4)(5)(6) and in patients (7)(8)(9) have shown that renal failure also decreases the metabolic clearance of drugs, particularly those metabolized by cytochrome P450 (CYP). The underlying causes of altered CYP functional expression observed in kidney disease remain unclear, but several studies indicate that uremic toxins4 ␤ -Hydroxycholesterol after kidney transplantation 2569 500 l of water and 2 ml of n-hexane were added, and extraction was performed by vortexing for 1 min.…”
mentioning
confidence: 99%
“…However, several studies in rats (1)(2)(3)(4)(5)(6) and in patients (7)(8)(9) have shown that renal failure also decreases the metabolic clearance of drugs, particularly those metabolized by cytochrome P450 (CYP). The underlying causes of altered CYP functional expression observed in kidney disease remain unclear, but several studies indicate that uremic toxins4 ␤ -Hydroxycholesterol after kidney transplantation 2569 500 l of water and 2 ml of n-hexane were added, and extraction was performed by vortexing for 1 min.…”
mentioning
confidence: 99%
“…A multitude of environmental, genetic, and physiologic factors are known to influence CYP3A4 expression and activity (Klein and Zanger, 2013). Several studies in rats (Rege et al, 2003;Kusaba et al, 2012;Velenosi et al, 2012) and in patients (Dowling et al, 2003;Kirwan et al, 2009Kirwan et al, , 2012 have shown that renal failure decreases CYP3A expression and function. We have previously reported a significant increase in plasma concentration of 4b-hydroxycholesterol as an endogenous marker of CYP3A activity in patients with end-stage renal disease after kidney transplantation (Suzuki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic metabolism of the compounds was evaluated in the incubation experiments with the rat and human liver microsomes in the same manner as previously reported 10,11 . In brief, the incubation mixture was prepared with phosphate buffer containing 250-500 mg of the microsomal protein.…”
Section: Evaluation Of the Hepatic Metabolism Of Rxr Agonistic Compoundsmentioning
confidence: 99%
“…The pooled liver microsomes were prepared with the ultracentrifugation method previously reported 10,11 . Male Wistar rats were obtained from Japan SLC Inc. (Hamamatsu, Japan).…”
Section: Preparation Of Liver Microsomesmentioning
confidence: 99%